Różne konteksty odmienności kobiet z niepełnosprawnością w twórczości plastycznej i percepcji dziecka we wczesnym wieku szkolnym = Various contexts of distinctness of women with disabilities in creativity and perception of a child in early school age - Banach, Iwona (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The functioning of the modern world determines the need for changes in education. We are starting to accept diversity and differences in many ascepts of our lives, instead of being a homogeneous society. One of the components of the category of "otherness" are people with disabilities and their functioning in different life structures. Education plays invaluable part in preparing human to meet disability, in terms of education and training.
Keywords: edukacja; niepełnosprawność; osoba z niepełnosprawnością; kobieta z niepełnosprawnością; education; disability; disabled people; disabled woman